PERAN PENDIDIK DALAM IMITASI BULLYING SEJAK DINI DI RUANG LINGKUP SEKOLAH DASAR - Rabiatul Adawiyah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
Bullying is behavior that is done consciously by someone to harass and hurt others. This research was reviewed to progress the minimization of bullying from an early age in the scope of elementary schools and to find out the role of educators in the character building of students with imitation bullying in the scope of elementary school education (SD). Which guides the role of the teacher figure as (1). Educators, (2) Teachers, (3) Facilitators, (4) Supervisors, (5) Servants, (6) Designers, (7) Managers, (8) Innovators, and (9) Assessors. This study uses the method of literature study.